1, 5, 7‐Triazabicyclo[4.4.0]dec‐5‐ene (TBD) Triggered Diastereoselective [3+2] Cycloaddition of Azomethine Imines and Pyrazoleamides. Issue 5 (23rd January 2019) - Volpe, Chiara; Meninno, Sara; Capobianco, Amedeo; Vigliotta, Giovanni; Lattanzi, Alessandra
Abstract: A practical and mild approach to prepare tetrahydropyrazolo[1, 2‐a]‐pyrazole‐1, 7‐diones, bearing up to three stereocentres, by reacting ready available N, N′ ‐cyclic azomethine imines and pyrazoleamides under catalytic loading of commercial 1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD), has been developed. The products are obtained in good yields and high diastereoselectivity, working at room temperature. Preliminary bioassay showed the products to inhibit growth of Gram‐positive bacteria. Abstract :